1997
DOI: 10.1128/jb.179.22.7135-7155.1997
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Methanobacterium thermoautotrophicum deltaH: functional analysis and comparative genomics

Abstract: Methanobacterium thermoautotrophicum ⌬H, isolated in 1971 from sewage sludge in Urbana, Ill. (72), is a lithoautotrophic, thermophilic archaeon that grows at temperatures ranging from 40 to 70°C and optimally at 65°C. M. thermoautotrophicum conserves energy by using H 2 to reduce CO 2 to CH 4 and synthesizes all of its cellular components from these same gaseous substrates plus N 2 or NH 4 ϩ and inorganic salts, but despite this impressive biosynthetic capacity, M. thermoautotrophicum ⌬H and related strains ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
811
1
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,114 publications
(835 citation statements)
references
References 71 publications
19
811
1
4
Order By: Relevance
“…We report here that the essential nucleolar protein Nop58p is specifically associated with one of the two major classes of snoRNAs, the box CϩD snoRNAs+ Immunoprecipitation using Nop58p epitope-tagged with Protein A efficiently precipitated all tested box CϩD snoRNAs+ The association of Nop58p with the box CϩD snoRNAs was found to be specific, since neither the box HϩACA snoRNAs nor the RNase MRP RNA were significantly coprecipitated+ In addition, Nop58p was shown to be required for the stability of the box CϩD snoRNAs; genetic depletion of Nop58p leads to the dramatic depletion of most box CϩD snoRNAs tested+ This effect was specific because neither the HϩACA snoRNAs nor the RNase MRP RNA were affected+ We conclude that Nop58p is a core component of the box CϩD snoRNPs, and is the first protein shown to be required for the stability of these RNA species+ UV crosslinking of box CϩD RNA reporter constructs in mouse nuclear extracts and Xenopus oocytes identified putative snoRNP proteins that require intact boxes C and D and the conserved 59-39 terminal stem for binding+ Among these were fibrillarin and a protein of 65-68 kD apparent molecular weight (Caffarelli et al+, 1998;Watkins et al+, 1998b), in good agreement with the predicted size of human Nop58p (Wu et al+, 1998)+ Searches of the complete genomic sequences of the Archaea Archaeoglobus fulgidus (Klenk et al+, 1997), Methanobacterium thermoautotrophicum (Smith et al+, 1997), and Methanococcus jannaschii (Bult et al+, 1996) identified predicted proteins in each organism with clear homology to Nop58p+ Comparison to the yeast/human alignments indicate that the archaeal proteins are rather FIGURE 8. Primer extension analysis of pre-rRNA processing in a GAL::nop58 strain+ Primer extension through the 59 ETS and ITS1 was performed using oligonucleotides a and e, respectively (see cartoon)+ Primer extension stops at the 59 end of the 59 ETS (ϩ1) and at sites A 0 , A 2 , A 3 , B 1L , and B 1S are indicated+ RNA was extracted from NOP58 and GAL::nop58 strains following growth on permissive rsg medium (0-h lanes) and at intervals following transfer to glucose medium (6-24-h lanes)+ more homologous to Nop58p than to Nop56p+ Homologs of the other common protein component of the box CϩD snoRNPs, Nop1p/fibrillarin, have previously been identified in Archaea (Amiri, 1994) and are also present in the complete genomic sequences+ Strikingly, the genes encoding the homologs of Nop58p and Nop1p appear to be cotranscribed as an operon in both A. fulgidus and M. thermoautotrophicum, strongly supporting their functional conservation+ In M. jannaschii the genes are closely located in the genome but do not appear to form an operon+ The presence and genomic organization of the homologs of both known box CϩD snoRNP proteins suggests that homologs of the box CϩD snoRNAs may also be present in Archaea (see Lafontaine & Tollervey, 1998 for further discussion)+ There are similarities between the proteins associated with the box CϩD and box HϩACA snoRNAs+ Both groups are associated with a protein that contains a glycine/arginine rich repeat (GAR domain or RGG box); the box CϩD snoRNAs are associated with Nop1p, and the box HϩACA snoRNAs with Gar1p+ Similarly, both groups are associated with proteins containing a KKD/E domain; Cbf5p (dyskerin in humans; Heiss et al+, 1998) is associated with the box HϩACA snoRNAs and Nop58p with the box CϩD snoRNAs...…”
Section: Discussionmentioning
confidence: 80%
“…We report here that the essential nucleolar protein Nop58p is specifically associated with one of the two major classes of snoRNAs, the box CϩD snoRNAs+ Immunoprecipitation using Nop58p epitope-tagged with Protein A efficiently precipitated all tested box CϩD snoRNAs+ The association of Nop58p with the box CϩD snoRNAs was found to be specific, since neither the box HϩACA snoRNAs nor the RNase MRP RNA were significantly coprecipitated+ In addition, Nop58p was shown to be required for the stability of the box CϩD snoRNAs; genetic depletion of Nop58p leads to the dramatic depletion of most box CϩD snoRNAs tested+ This effect was specific because neither the HϩACA snoRNAs nor the RNase MRP RNA were affected+ We conclude that Nop58p is a core component of the box CϩD snoRNPs, and is the first protein shown to be required for the stability of these RNA species+ UV crosslinking of box CϩD RNA reporter constructs in mouse nuclear extracts and Xenopus oocytes identified putative snoRNP proteins that require intact boxes C and D and the conserved 59-39 terminal stem for binding+ Among these were fibrillarin and a protein of 65-68 kD apparent molecular weight (Caffarelli et al+, 1998;Watkins et al+, 1998b), in good agreement with the predicted size of human Nop58p (Wu et al+, 1998)+ Searches of the complete genomic sequences of the Archaea Archaeoglobus fulgidus (Klenk et al+, 1997), Methanobacterium thermoautotrophicum (Smith et al+, 1997), and Methanococcus jannaschii (Bult et al+, 1996) identified predicted proteins in each organism with clear homology to Nop58p+ Comparison to the yeast/human alignments indicate that the archaeal proteins are rather FIGURE 8. Primer extension analysis of pre-rRNA processing in a GAL::nop58 strain+ Primer extension through the 59 ETS and ITS1 was performed using oligonucleotides a and e, respectively (see cartoon)+ Primer extension stops at the 59 end of the 59 ETS (ϩ1) and at sites A 0 , A 2 , A 3 , B 1L , and B 1S are indicated+ RNA was extracted from NOP58 and GAL::nop58 strains following growth on permissive rsg medium (0-h lanes) and at intervals following transfer to glucose medium (6-24-h lanes)+ more homologous to Nop58p than to Nop56p+ Homologs of the other common protein component of the box CϩD snoRNPs, Nop1p/fibrillarin, have previously been identified in Archaea (Amiri, 1994) and are also present in the complete genomic sequences+ Strikingly, the genes encoding the homologs of Nop58p and Nop1p appear to be cotranscribed as an operon in both A. fulgidus and M. thermoautotrophicum, strongly supporting their functional conservation+ In M. jannaschii the genes are closely located in the genome but do not appear to form an operon+ The presence and genomic organization of the homologs of both known box CϩD snoRNP proteins suggests that homologs of the box CϩD snoRNAs may also be present in Archaea (see Lafontaine & Tollervey, 1998 for further discussion)+ There are similarities between the proteins associated with the box CϩD and box HϩACA snoRNAs+ Both groups are associated with a protein that contains a glycine/arginine rich repeat (GAR domain or RGG box); the box CϩD snoRNAs are associated with Nop1p, and the box HϩACA snoRNAs with Gar1p+ Similarly, both groups are associated with proteins containing a KKD/E domain; Cbf5p (dyskerin in humans; Heiss et al+, 1998) is associated with the box HϩACA snoRNAs and Nop58p with the box CϩD snoRNAs...…”
Section: Discussionmentioning
confidence: 80%
“…Given that the functional intersection of the three domains, as presented herein, is based only on one species which certainly does not embrace the full diversity of Archaea, the universal function set is expected to grow as more complete genomes become available (Klenk et al 1997;Smith et al 1997). There exist, for instance, genes in A. fulgidus and M. thermoautotrophicum that are present in the other two domains but are absent from M. jannaschii (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This common sequence was denoted the "leader" and is usually ATrich 14 . Similar to the repeats, leaders lack an open reading frame and are generally not conserved between species; however, when several CRISPR loci are found in the same chromosome their leaders can be conserved 8,27,28 . When a new repeat-spacer unit is added to the CRISPR array, it almost always occurs between the leader and the previous unit, suggesting that the leader might function as a recognition sequence for the addition of new spacers 19,21 .…”
Section: Structural Features Of Crispr Systemsmentioning
confidence: 99%